Diversity of Mollusca and Fish in Gondoor and Nakane Lakes in Dhulia, Northwest Maharashtra, India - Lohar, Madhusudan V. Amrutsagar*; Prakash S. (Journal of Ecobiotechnology, 2011)
Molluscan and fish diversity of the lake Gondoor and Nakane in northwest Maharashtra have been studies during June 2008 to May 2010. A total of 17 species of molluscs and 18 fish species were recorded from both lakes. The dominant class Gastropoda of Mollusca was dominated by 14 species including Pila globosa, Thiara scabra, Melanoides tuberculata, Bellamya bengalensis, Lymnaea accuminata, Lymnaea lutiola, Indoplanarbis exustus, Zootecus insularis, Tarebia lineate Cerastua maussonianus Filicaulis alte, Laevicaulis alte, Senperula maculata and Rachis punctatus. Pelecypoda is another class of mollusc represented by 3 species including Perrysia caerulea, Lemellidens corianus and Corbicula striatella. Ichthyofauna of Gondoor and Nakane lakes were dominated by major carps with 10 members belonging to cypriniformes including Labeo rohita, Catla catla, Cyprinus carpeo, Cirrhinus marigala, Labeo calbasu, Labeo bata, Labeo fimbriatus, Puntius sarana followed by 6 members of family siluriformes including Clarius batrachus, Mystus bleekeri,Ã‚Â Mystus vittatus, Ompak bimaculatus, Wallago attu, Heteropnoustes fossilis, Amblypharyngodon mola, Puntius sophore and one genera with two species of family channiformes represented by Channa punctatus and Channa striatus. Both lakes are precious aquatic ecosystem playing significant role in supplying drinking water to Dhule as well as sustain a rich molluscan and fish fauna.